Trust as Element of Life Insurance Market Structure - Юлия Николаевна Никитина (Journal of Economic Sociology, 2010)
The author focuses on the analysis of the forms and the role of trust in the structure of the market of the services of life insurance. Particularly on this market we could easily trace the role of trust. As we trust the insurance company not only money but our lives. The question is how much a consumer has to trust the company in this case? The research is done on the basis of the expert interviews and R-TGI data.